OP11 Longitudinal profiling of mucosal immune cell composition using multiplex immunohistochemistry identifies drug- and response-specific patterns in Ulcerative Colitis. (27th May 2021) - Volk, V; Aden, K; Tran, F; Mishra, N; Bernardes, J; Röcken, C; Schreiber, S; Feuerhake, F; Rosenstiel, P
Abstract: Background: Interventions targeting key inflammatory mechanisms have expanded the therapeutic repertoire for ulcerative colitis (UC). However, exact molecular mechanisms associated with clinical response remain elusive. We conducted a multiplex-immunohistochemistry (IHC) study to monitor immune cell composition in biopsies from UC patients under 2 approved therapies targeting TNF (infliximab) and integrin (vedolizumab), and a phase IIa clinical trial with the selective IL-6 transsignalling inhibitor olamkicept, to identify spatiotemporal changes of mucosal immune cell compartments in relation to each mechanism of action. Methods: Sigmoid biopsies from UC patients exposed to infliximab, vedolizumab or olamkicept (26 patients in total) at baseline and week 2, 6 and 14 after therapy induction were subjected to multiplex IHC for CD3, CD15, CD20, CD68, pSTAT3, and pan-cytokeratin (OPAL/Vectra Polaris, Akoya). Quantitative and spatial immune cell patterns captured by advanced image analysis (inForm, Akoya; R package PhenoptrReports) were analysed for differences between baseline and subsequent time points using Dunnett's multiple comparisons test (GraphPad Prism 8.4.3). Accepted significance levels: *p<0.05, **p<0.01, ***p<0.001. Results: Targeted therapies resulted in overall decrease of immune cell infiltrates (range 1.15–1.22 fold; p=0.017-0.007), irrespective of drug or specified endpoint (remission at week 14) (Fig. 1). Significant drug-specific changes of spatial immune cell distributions were discernible (Fig. 2). Anti-TNF treatment was mainly associated with decrease in CD3 + T cells (p=0.005) localized in the submucosa close to epithelium or in tertiary lymphoid organs. In contrast, integrin targeting resulted in fewer CD15 + neutrophils, mainly in the submucosal compartment (p=0.046). Olamkicept treatment resulted in unique depletion of pSTAT3 + cells in patients achieving remission at week 14 (not observed in remission after infliximab or vedolizumab). To decipher drug-independent features of clinical remission we assessed distance metrics between immune and intestinal epithelial cells in remission and non-remission patients and observed increase (endpoint compared to baseline) of the average distance to the nearest CD20 or CD15 cell in the remission (p=0.0054, p=0.0004) but not in the non-remission group (n.s.). Conclusion: Our study strongly suggests that multiplexed spatiotemporally resolved immune cell phenotyping may provide novel insights into the dynamic shifts of immune cell compartments in UC patients undergoing targeted therapy. We propose that such highly resolved digital maps of immune cells could lead to novel tools for therapeutic stratification of IBD patients.